Biomimetic total syntheses of flinderoles B and C - Dethe, Dattatraya H.; Erande, Rohan D.; Ranjan, Alok (Journal of the American Chemical Society, 2011)
A simple and efficient biomimetic synthesis of pyrrolo[1,2-a]indoles using a highly stereo- and regioselective [3 + 2] reaction cascade was developed and then further applied in the first total synthesis of flinderoles B and C, which proceeded in 17.2% yield over the longest linear sequence of 11 steps.